Effect of Bioactive Compounds of Sting Nettle (Urtica Diocia L.) Leaves on Shelf Life of the Salty Biscuits - Shaimaa, M. Hassan (Food Technology Research Journal)
Stinging nettle (Urtica dioica) is an edible plant, well-known for its nutraceutical properties. Stinging nettle leaves are typically rich in fibers, minerals and vitamins, as well study was to evaluate the sensory properties and the rheological properties of wheat salted biscuits after adding of dried nettle leaves to flour wheat at different concentrations of 5,10 and 15 % antioxidant compounds, i.e., phenols and flavonoid. along with the control sample. Also, changes in the microbial load of biscuits added to nettle leaves during storage periods (1,3,6 and zero time) were investigated. Showed that total bacterial counts were not detected at all directly after processing with all used concentration increased gradually with time. At 5%, and 10% concentration, total bacterial count appeared a month later zero time. During storage period, total bacterial count appeared and a month later with (3.08 and 2.30 log cfu/g) and increased gradually to reach (3.34 and 2.77 log cfu/g) respectively, while 6 months later of storage, total bacterial counts increased gradually reaching (5.50, 4.91 and 4.56 log cfu/g) with concentrations 5%,10% and 15% respectively compared to control. It means that, 15% can be enough as preservation treatment for biscuits. concentration with 15% had higher effect, where total bacterial counts appeared after 3 months (2.30 log cfu/g) and increased to (4.65 log cfu/g) after 6 months of storage. fungi was not detected (ND) through increasing time of storage due to the low moisture in biscuits samples and reducing the numbers of fungies in the various concentrations of nettle leaf. The antimicrobial activity of ethanolic and methanolic extracts of nettle they demonstrated no effects against yeast-like fungi (Candida albicans). Although all extracts exhibited an antimicrobial activity against all tested bacteria with inhibition zones ranging from 10.0±0.58 to 12.7±0.67 mm., they were more effective against gram-positive bacteria (Bacillus cereus and Staphylococcus aureus) than against gram gram-negative bacteria (Salmonella typhimurium and Escherichia coli).